A review of specialties performing temporal artery biopsies in Ontario: a retrospective cohort study - Micieli, Jonathan A.; Micieli, Robert; Margolin, Edward A. (CMAJ Open, 2015)
Background Temporal artery biopsy is the gold standard for the diagnosis of giant cell arteritis, but the numbers and types of surgical specialists performing temporal artery biopsies are unknown. The goal of this study was to determine which surgical specialists performed temporal artery biopsies and how geographic location influenced this trend over a period of 10 years.Methods This retrospective cohort study included all physicians practising in Ontario from 2002 to 2013. Using comprehensive physician services data from the IntelliHEALTH Medical Services database, physicians performing temporal artery biopsies were identified by the Ontario Health Insurance Plan billing code submitted for remuneration. Physicians were categorized by specialty and geographic Local Health Integration Unit.Results A total of 9958 patients underwent a temporal artery biopsy during the study period: the biopsies were performed by 11 different subspecialties. The number of patients undergoing a temporal artery biopsy declined over the 10-year study period. Most procedures were performed by general surgeons (38.1%), followed by ophthalmologists (31.0%) and plastic surgeons (23.6%). Ophthalmologists performed more temporal artery biopsies per person compared with general surgeons, but significantly more general surgeons performed at least 1 biopsy. There was significant variation based on geographic location: plastic surgeons performed the most biopsies in regions with a population of more than 1 million people, and general surgeons performed most of the biopsies in rural areas.Interpretation Geographic location heavily influenced which specialty was most likely to perform temporal artery biopsies. General surgery, ophthalmology and plastic surgery emerged as leaders in this area, and their residency programs should include formal training in this procedure in their curricula.